Chinese Americans' perceptions of race, education, and affirmative action - Lin, Shasha (Springer Nature Switzerland, 2025)
Chapter 1. Introduction: Justice to Them Is Injustice to Us -- Chapter 2. Education is the Only Way Out -- Chapter 3. The Asian Penalty: A Shared Reality? -- Chapter 4. A History of Complex Positioning -- Chapter 5. Making Sense of Affirmative Action -- Chapter 6. Beyond Affirmative Action: Fairness and Institutional Trust -- Chapter 7. Higher Education in the Post-Affirmative Action Era.
Gesehen am 25.09.2025
Keywords: Hochschulschrift